Oleanane-type triterpenoid: an anti-inflammatory compound of the roots Arrabidaea brachypoda - Rocha, Cludia Q. da [UNESP]; Vilela, Fabiana C.; Santa-Cecilia, Flavia V.; Cavalcante, Gustavo P.; Vilegas, Wagner [UNESP]; Giusti-Paiva, Alexandre; Santos, Marcelo H. dos (Soc Brasileira Farmacognosia, 2015)
Arrabidaea brachypoda Bureau, Bignoniaceae, known as cipo-una, is widely used in traditional medicine in Southeastern and Northeastern Brazil for kidney stones and painful joints. This study was aimed at evaluating the anti-inflammatory proprieties of the oleanane-type triterpenoid 3 beta-estearioxy-olean-12-ene isolated from the roots of A. brachypoda. Carrageenan-induced paw oedema, formalin test and hot plate test were used to investigate the antiinflammatory activity of 3 beta-estearioxy-olean-12-ene in animals. We observed that 3 beta-estearioxy-olean-12-ene at doses of 5, 10 and 15 mg/kg p.o. demonstrated anti-inflammatory effects, by reduced (p < 0.05) paw oedema induced by carrageenan and by decreased (p < 0.05) licking time caused by a subplantar injection of formalin. In conclusion, 3 beta-estearioxy-olean-12-ene, a triterpene isolated from the roots of A. brachypoda, demonstrate anti-inflammatory effect indifferent tests. Thus, it may be useful in the treatment of inflammatory disorders, which supports previous claims of its traditional use. (C) 2015 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Arrabidaea brachypoda; Inflammation; Natural product; Pain; Triterpene